Automated water tank filtration system using LDR sensor - Ibrahim, S.Noorjannah; Lokman Hakim, M.S.; Asnawi, Ani Liza; Malik, Naheed A. (IEEE, 2016)
In this paper, we present the development of an automated water tank filtration system together with the study on water turbidity using light dependent resistor (LDR) as the sensing unit. The system comprises of a microcontroller (Arduino Uno), a micropump, a sensing unit and a water filter. The main objective of this paper is to study the ability of LDR sensing unit in detecting changes in water and to define the turbidity value of the water. This paper also described how the microcontroller controls the filtration system. Experiments on water turbidity was conducted under two conditions, undisturbed flow and continuous flow, which will affect the measurements of the LDR. Results show that the LDR readings in continuous flow require more time in between reading so that the turbidity value can be consistent. Results show that the LDR sensing together with the microcontroller can create a system that is capable of measuring water turbidity not only for water tanks but also for other water resources e.g. rivers, lakes, treatment plants etc. The implementation of an automated water filtration system can potentially help consumers in monitoring their water tanks and can be included in the smart home system.